Development of a Component-Level Hydrogen Transport Model with OpenFOAM and Application to Tritium Transport Inside a DEMO HCPB Breeder - Volker Pasler; Frederik Arbeiter; Christine Klein; Dmitry Klimenko; Georg Schlindwein; Axel von der Weth (Applied Sciences, 2021)
This work continues the development of a numerical model to simulate transient tritium transport on the breeder zone (BZ) level for the EU helium-cooled pebble bed (HCPB) concept for DEMO. The basis of the model is the open-source field operation and manipulation framework, OpenFOAM. The key output quantities of the model are the tritium concentration in the purge gas and in the coolant and the tritium inventory inside the BZ structure. New model features are briefly summarized. As a first relevant application a simulation of tritium transport for a single pin out of the KIT HCPB design for DEMO is presented. A variety of scenarios investigates the impact of the permeation regime (diffusion-limited vs. surface-limited), of an additional hydrogen content of 300 Pa H2 in the purge gas, of the released species (HT vs. T2), and of the choice of species-specific rate constants (recombination constant of HT set twice as for H2 and T2). The results indicate that the released species plays a minor role for permeation. Both permeation and inventory show a considerable dependence on a possible hydrogen addition in the purge gas. An enhanced HT recombination constant reduces steel T inventories and, in the diffusion-limited case, also permeation significantly. Scenarios with 80 bar vs. 2 bar purge gas pressure indicate that purge gas volumetric flow is decisive for permeation.